Site-specific hydrogen exchange of proteins: insights into the structures of amyloidogenic intermediates. - Yao, Z; Tito, P; Robinson, C (2005)
We describe the use of nano-electrospray ionization (nano-ESI) mass spectrometry (MS) for monitoring hydrogen exchange. Using this approach, we have compared the fluctuations in structure of the wild-type human lysozyme with those of the Asp67His and Ile56Thr variants, the two amyloidogenic forms of the protein. The results revealed that a significant region of the structure was transiently unfolded in both variants compared with the wild-type protein. Using peptic digestion, we located the region of the protein involved in the unfolding reaction to the beta-domain and adjacent C-helix. This unfolding reaction is proposed to facilitate the initial stages of the fibril formation process. Also by this approach, we discovered that binding of an antibody fragment to the proteins prevents the unfolding events. These observations, therefore, not only highlight the use of MS to monitor and locate regions of enhanced hydrogen exchange kinetics, even in proteins that are prone to aggregation, but also demonstrate the use of such an approach to discover potential therapies.